Kidney pathology in COVID-19 patients - A. V. Kiseleva; A. V. Leskova; V. V. Skvortsov (Лечащий Врач, 2022)
Coronaviruses are highly contagious and highly tropic to the kidney tissue. A new coronavirus infection can cause a wide range of pathological abnormalities of the kidneys, which is due to the content in the organs of angiotensin converting enzyme type 2 (ACE2), transmembrane serine protease 2 and cathepsin L, which are considered a target for SARS-CoV-2. Clinical manifestations vary from mild forms of acute respiratory viral infection to severe multiple organ lesions. Various clinical forms of kidney damage in COVID-19 are due to numerous pathogenetic mechanisms, such as the direct cytopathic effect of the virus on kidney structures, endothelial dysfunction, cytokine storm, hemodynamic and water metabolism disorders, and damage to the renin-angiotensin-aldosterone system. SARS-CoV-2 interacts with ACE2 receptors located on the endothelium of blood vessels, adversely affecting the microvascular bed. In addition, damage to the renal tissue is caused by the synthesis of pro-inflammatory interleukins, as well as hypovolemia and the accumulation of angiotensin II and bradykinin. Kidney damage in patients with COVID-19 includes such nosological forms as collapsing nephropathy, minimal change disease, membranous glomerulopathy, anti-GBM nephritis, acute tubular necrosis, exacerbation of autoimmune glomerulonephritis, allograft rejection. During clinical observations, scientists from different countries have established a relationship between confirmed COVID-19 and the following laboratory data: hematuria, proteinuria, elevated levels of blood urea nitrogen, serum creatinine, uric acid, D-dimer. Recent studies show that patients with coronavirus often suffer from kidney failure, which is closely associated with higher mortality and morbidity and is an indicator of survival in coronavirus infection. In addition, the presence of such risk factors in a patient as chronic kidney disease, cardiovascular pathology, the presence of immunodeficiency states, the use of nephrotoxic drugs, diabetes mellitus, hypertension, obesity, atherosclerosis, and advanced age complicate the course of infection and worsen the prognosis of the disease. Thus, the pathological effect of coronavirus on the body and on the kidneys, in particular, as well as high mortality among patients with renal pathology, determines the relevance of studying this problem and finding ways to solve it.